Discurso e poder de corpos insepultos a partir do mito de Antígona - Krautchuk, Camila Ratki (2021)
Assuming that Antigone's speeches (442 BC) of Sophocles' Greek tragedy – that he wanted to bury his brother's body – is an event that resonates in countless narratives, rewrites, comments and interpretations, we propose in this study focus on the scene of Oedipus' daughter's disobedience before the king and analyze its timeliness in other narratives in which a woman clashes with sober power because it is her "obligation" to bury a dead person, to give him a grave. We propose to revisit this myth and analyze, from the perspective of Foucautian Discursive Studies, the event of her return in narratives in which the woman stands out for transgression and disobedience. In this direction, we make visible especially the memories built about Zuleika Angel Jones (1921-1976), Zuzu Angel, a famous fashion designer who became a political activist in the lead years of the Brazilian military dictatorship. After her son's disappearance and the certainty that he was dead, she wages a real battle against the regime of the time in a tireless, courageous and disobedient search – like Antigone – for the search of her son's body. In addition to the Zuzu Angel are the mothers of Square of May who were looking for – and still are looking for – the children lost during an Argentine military dictatorship. Thus, the main objective of the dissertation is to analyze and describe the speeches about the unburied body that interdiscursively approach as enrolled women – children disappeared (were killed) under the exercise of dictatorial power – from Antigone, taking “disobedience” as a special pairing element. Our analytical path will allow us, in addition to explaining the fundamental concepts of Foucault's Archegenealogy, to think about the subjectivity of these women in the discontinuities of history and, in particular, to analyze the memory (and the will to truth) of Antigone's discourses around the discursive event of burying the body being updated in the speeches of these mothers years later.